2013
DOI: 10.1111/ijfs.12207
|View full text |Cite
|
Sign up to set email alerts
|

Influence of viticultural practices and winemaking technologies on phenolic composition and sensory characteristics of Negroamaro red wines

Abstract: Summary The aim of this study was to assess the impact of some viticultural practices (VP) and winemaking technologies (WT) on phenolic composition and sensory characteristics of Negroamaro wines produced in Apulia, Southern Italy. Among VP, two soil management (cover crop and soil tillage) and two training systems (bilateral cordon and unilateral cordon) were compared, whereas among WT, three vinifications were tested: control (traditional, 7 days of maceration at 25 °C with two daily punching‐down), cryomace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 47 publications
(41 reference statements)
1
29
0
Order By: Relevance
“…Anthocyanin composition was determined by HPLC‐DAD according to Coletta et al. (), and results were expressed as mg/L of malvidin‐3‐ O ‐glucoside equivalent. Antioxidant activity (AA) was assessed using ABTS [2,2′‐azino‐bis(3‐ ethylbenzothiazoline‐6‐sulfonic acid)] assay as reported by Trani, Verrastro, Punzi, Faccia, and Gambacorta (), and results were expressed as μM Trolox equivalent antioxidant capacity (TEAC).…”
Section: Methodsmentioning
confidence: 99%
“…Anthocyanin composition was determined by HPLC‐DAD according to Coletta et al. (), and results were expressed as mg/L of malvidin‐3‐ O ‐glucoside equivalent. Antioxidant activity (AA) was assessed using ABTS [2,2′‐azino‐bis(3‐ ethylbenzothiazoline‐6‐sulfonic acid)] assay as reported by Trani, Verrastro, Punzi, Faccia, and Gambacorta (), and results were expressed as μM Trolox equivalent antioxidant capacity (TEAC).…”
Section: Methodsmentioning
confidence: 99%
“…Detection was performed at 520 nm, and quantification was made according to external standard method on the basis of standard calibration curve obtained by the injection of solutions at different concentration of cyanidin 3-O-glucoside (R 2 = 0.9991). Tentative identification of anthocyanin compounds was achieved by combining elution pattern, UV-Vis spectra and data reported in literature (Abdel-Aal et al, 2006;Coletta et al, 2013). Results were expressed as mg/kg.…”
Section: Determination Of Anthocyanin Profilementioning
confidence: 99%
“…Currently, agricultural and industrial residues such as buckwheat, almond hulls, straw and fruit peels, grape seed and grape skins are primary sources for obtaining valuable compounds [22][23][24][25]. Pan et al [26] demonstrated that UAE was an effective, reliable and feasible method for extracting the phenolic compounds from hawthorn seed with better results than classical extraction.…”
Section: Introductionmentioning
confidence: 99%